2018
DOI: 10.1038/s41396-018-0288-5
|View full text |Cite
|
Sign up to set email alerts
|

Modeling microbial communities from atrazine contaminated soils promotes the development of biostimulation solutions

Abstract: Microbial communities play a vital role in biogeochemical cycles, allowing the biodegradation of a wide range of pollutants. The composition of the community and the interactions between its members affect degradation rate and determine the identity of the final products. Here, we demonstrate the application of sequencing technologies and metabolic modeling approaches towards enhancing biodegradation of atrazine-a herbicide causing environmental pollution. Treatment of agriculture soil with atrazine is shown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
90
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 80 publications
2
90
0
Order By: Relevance
“…When evaluating the mineralization potential of the s -triazinic cycle, results are quite contrasted with a significant increase of the mineralization potential in the atrazine only supplemented medium (from 48.3 %; CI 95% =[36.5 – 60] to 86.9 %; CI 95% =[81.6 – 92.2]), and significant decreases or no change in the two and three nitrogen sources supplemented media. Altogether, these results indicate that the upper part of the atrazine degradation pathway ( atzA , trzN , atzB and atzC ) has been improved in the evolved consortia, presumably leading to increased intermediary metabolite production, such as aminoethanol, ethylamine or hypoxanthine 18 . While the upper pathway is constitutively expressed, studies have shown that the lower pathway was repressed by the presence of ammonium in the environment 23 .…”
Section: Textmentioning
confidence: 75%
See 1 more Smart Citation
“…When evaluating the mineralization potential of the s -triazinic cycle, results are quite contrasted with a significant increase of the mineralization potential in the atrazine only supplemented medium (from 48.3 %; CI 95% =[36.5 – 60] to 86.9 %; CI 95% =[81.6 – 92.2]), and significant decreases or no change in the two and three nitrogen sources supplemented media. Altogether, these results indicate that the upper part of the atrazine degradation pathway ( atzA , trzN , atzB and atzC ) has been improved in the evolved consortia, presumably leading to increased intermediary metabolite production, such as aminoethanol, ethylamine or hypoxanthine 18 . While the upper pathway is constitutively expressed, studies have shown that the lower pathway was repressed by the presence of ammonium in the environment 23 .…”
Section: Textmentioning
confidence: 75%
“…However, in nitrogen limited environments, atrazine degrading capacities must be conserved because mineralization of atrazine leads to the essential delivery of nitrogen 17 . Also, exchange of metabolites, such as desisopropylamine, aminoethanol and desethylamine, are produced and released in the environment during atrazine degradation 18 . Therefore, atrazine biodegradation is a good candidate function to test the BQH predictions, and in particular the emergence of dependency between species in a spatially unstructured environment.…”
Section: Textmentioning
confidence: 99%
“…Additionally, we demonstrate that through using metabolic time dependent simulations, an optimal range of nutrient augmentation may also be planned. Though soil communities are complex in terms of their composition and microbial consortia dynamics, in a recent study we demonstrated the usefulness of modeling approaches for deciphering metabolic complexities 44 , pointing at the future potential of modeling approaches. Despite the complexity of soil communities, supplementing soil with carbon sources is long known to induce a change in microbial structure and function.…”
Section: Discussionmentioning
confidence: 88%
“…To this end, we simulated the behavior of our metabolic model across time. This was done as described in 44 and illustrated in Supplemental data 5, based on concepts defined in 63 . Briefly, the model works under the following assumptions: (1) A finite start amount of media components is available; (2) A maximal amount of uptake a single cell can acquire from the media in a given time point is defined (the lower bound of the exchange reaction value); (3) New substrate concentrations in time t, are determined by the predicted substrate concentration for the previous step augmented with any additional substrates provided or consumed in the current iteration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation